PpSKα boosts chilling tolerance by activating PpTrxh9 in peach fruit - Jiao, Caifeng; Sun, Jing (Frontiers in Plant Science, 2025)
IntroductionThe cold chain system is extensively used to lower the quality deterioration in postharvest fruits. However, the occurrence of chilling injury (CI) is a common phenomenon in peach fruits, consequently compromising their market value.Methods and resultsCold tolerance was boosted by glycine betaine (GB) supplementation. GB treatment promoted the thioredoxin h9 (PpTrxh9) expression and ameliorated oxidative injury. Using assays such as yeast two-hybrid, co-immunoprecipitation, pull-down, and bimolecular fluorescence complementation, SHAGGY-related protein kinase a (PpSKa) was verified as a protein interacting with PpTrxh9. GB treatment elevated the PpSKa expression. The overexpression of PpSKa in tomato fruits decreased the cold sensitivity and oxidative damage, whereas virus-induced gene silencing of PpSKa in peach fruits aggravated the CI progression and oxidative damage. PpSKa was found to phosphorylate PpTrxh9 in the kinase assay. Moreover, PpSKa-overexpressed tomato fruits exhibited higher SlTrxh9 expression, whereas the PpSKa-RNAi peach fruit exhibited lower PpTrxh9 expression.DiscussionTaken together, PpSKa decreased the development of CI by improving the expression of PpTrxh9 in peach fruits.